Patient perspectives of artificial intelligence as a medical device in a skin cancer pathway - Kawsar, Anusuya; Hussain, Khawar; Kalsi, Dilraj; Kemos, Polychronis; Marsden, Helen; Thomas, Lucy (Frontiers in Medicine, 2023)
and is also part of the AI provider clinical advisory group.Author Contributions: AK and KH led the patient data interpretation and wrote the paper. DK led the study results interpretation. PK provided statistical input into the study design and conducted the statistical analysis. HM designed and ran the study and supported the data interpretation throughout. LT was the study Chief Investigator and provided dermatologist input throughout the study. All authors have reviewed and provided input into the paper.The study was funded by Skin Analytics Ltd, as part of a grant from InnovateUK 4. Acknowledgments: The authors would like to thank all patients who consented to the study and completed the patient survey; Chelsea and Westminster Hospital staff involved in patient recruitment, data collection, and diagnosis confirmation; and Skin Analytics staff involved in the development of the AIaMD and the operations of the study.